Creating Integrated Financial Statements Through Good Corporate Governance: The Active Role of Earning Management as An Intervening Variable - Sriyono Sriyono; Supardi Supardi; Detak Prapanca; Hanifah Novia Sofi (Fakultas Ekonomi, Universitas Bangka Belitung, 2022)
Many previous researchers have carried out research on the integrity of financial statements. The newness of this study is to use profit management as an intervening variable, where this research has not been carried out. Therefore,this research will be important information for company management for creating integrated financialstatements. The purpose of this study isto determine whether earningsmanagementcanbecomeaninterveningvariabletowardsanintegratedreportthroughthecomponents of good corporate governance. This type of research is quantitative research, thepopulationusedismanufacturingcompanieslistedontheIndonesiaStockExchange.Thesampling technique used is purposive sampling. The data analysis technique used is to test theclassicalassumptionsfirst,thentesttheestimationofthepaneldataregressionmodelandthentestthe hypothesis analysis with the t-test. The analysis results found a relationship between severalcomponents of good corporate governance that can affect the integrity of financial statements,including institutional ownership, managerial ownership, and independent commissioners andearnings management. The conclusion obtained is that the Earning management variable is not able tomediate thestrengtheningof theintegrityof financial statements report